Synthetic evaluation of standard and microwave-assisted solid phase peptide synthesis of a long chimeric peptide derived from four Plasmodium falciparum proteins (2018)
An 82-residue-long chimeric peptide was synthesised by solid phase peptide synthesis (SPPS), following the Fmoc protocol. Microwave (MW) radiation-assisted synthesis was compared to standard synthesis using low loading (0.20 mmol/g) of polyethylene glycol (PEG) resin. Similar synthetic difficulties were found when the chimeric peptide was obtained via these two reaction conditions, indicating that such difficulties were inherent to the sequence and could not be resolved using MW; by contrast, the number of coupling cycles and total reaction time became reduced whilst crude yield and percentage recovery after purification were higher for MW radiation-assisted synthesis. © 2018 by the authors.